Theorems on Inclusion for Multivalued Mappings - Zelinskii, Yu. B.; Klishchuk, B. A.; Tkachuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The paper is devoted to the investigation of some properties of multivalued mappings in Euclidean spaces. Fixed-point theorems are proved for multivalued mappings whose restrictions to a certain subset in the closure of a domain satisfy a “coacute angle condition” or a “strict coacute angle condition.” Similar results for the restrictions of multivalued mappings satisfying certain metric conditions are also obtained.